PENGARUH KARAKTERISTIK PERSONAL TERHADAP DYSFUNCTIONAL AUDIT BEHAVIOR - Mellisa Arviana; Yvonne Augustine (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
Dysfunctional audit behavior is any action taken in the implementation of the auditor's audit program that can reduce or degrade the quality of audits, either directly or indirectly. Auditor’s personal characteristics that affect the acceptance of dysfunctional audit behavior is the locus of control, organizational commitment, and turnover intentions. The purpose of this research was to determine the influence of auditors’ personal characteristics on acceptance of dysfunctional audit behavior. Data for this research is the primary data obtained through the process of filling out the questionnaire. The population for this research is the external auditors who work at various public accounting firm and internal auditors who work in various companies in Indonesia.. The hypothesis is tested by the multiple regression method using SPSS statistical tool version 22, the result of this research indicate that the locus of control has significant positive effect to the acceptance of dysfunctional audit behavior, organization commitment has negative effect to the acceptance of dysfunctional audit behavior, and organizational commitment has positive impact on behavior audit dysfunction with mediation turnover intention.